“MITRA IN AVESTA : MORAL, SOCIAL, AND JUSTISE FUNCTIONS” (International Conference on Education, Psychology and Humanities, 2026)
In Zoroastrianism, the deity Mitra (Mihr) occupies a prominent and multifaceted position within the sacred corpus of the Avesta. Far from being a peripheral figure in the ancient Indo-Iranian pantheon, Mitra functions as a central guarantor of cosmic, moral, and social order. Within the Avestan texts, Mitra’s role is articulated through a complex interplay of juridical, ethical, and ritual functions, emphasizing his authority over covenants, promises, and the maintenance of harmonious relationships among human beings, as well as between humanity and the divine.
Keywords: cosmic, moral, and social order.